Supplement to Draft Annual Plan 1976-77 Himachal Pradesh (Data-Base Accompaniment) - Planning Commission (Planning Commission, 1976)
Draft Annual Plan 1970—77 Agriculture Scheme-Outlays & Expenditure Selected Progresses Targets and Achievement Foodgrains and Commercial Crops Targets and Achievements Minor Irrigation, List of Schemes Included the Sub-Plan 1976-77 Targets of Production and Selected Physical Programme Milk Plant-Targets and Achievements Fisheries Development Schemes-Outlays and Expenditure Schemes of Forestry Development-Targets and Achievements Community Development and Panchayat Raj Schemes-Outlays Expenditure Physical Targets and Achievements.
Planning Department, Himachal Pradesh